1883 Ariz. Sess. Laws 65–66, ch. 36 - (:unkn) unknown (General Publisher, 1883)
Prohibited any person over the age of ten but under the age of seventeen from carrying any dirk, dirk-knife, Bowie-knife, slung-shot, brass knuckles, or pistol.
--
Keywords: POSSESSION - MINORS